Fillers in Mark Zuckerberg’s Interview on Cleo Abram’s Podcast - Aditya Diaz Ilyasa; Widhiyanto Widhiyanto (Institut Agama Islam Negeri (IAIN) Manado, 2026)
This study analyzes a 48-minute podcast episode on Cleo Abram's YouTube channel featuring Mark Zuckerberg, aiming to reveal the types of fillers used and their functions in the context of informal digital communication featuring a technology industry figure discussing complex technological topics. A descriptive qualitative approach supported by simple quantification was employed, using Rose's (1998) and Stenström's (1994) frameworks for analysis. Repeated coding was conducted to ensure intra-rater reliability.